Lemko becoming a nation = Łemkowskie "stawanie się" narodem - Dudra, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The process of creating the Lemko nation began in the sixteenth century, with the birth of Lemko literature and the development of literary life in the second half of the nine-teenth century. Qeir language and literature alongside the history and culture became the chief drivers of developing the nation. Qe universal sense of Lemko nationality was in progress as until 1944 in the Lemko homeland (area the Beskid Niski and Sadecki). It was interrupted by the expulsion on grounds of the USSR (1944-1946) and the events associated with the "Wisła" action (1947). Later, due to the threat of identity, national revival among the Lemkos accelerated.
Keywords: nation; identity; national identity; assimilation; nationalism; naród; tożsamość; tożsamość narodowa; asymilacja; nacjonalizm